Investasi Pendidikan sebagai Pengembangan Sumberdaya Manusia - Slamet, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2006)
A nationwide survey in Indonesia confirmed that investment on education not merely economically-sound but also socio-culturally beneficial. The spiral effect of investment on education, in return enhance economic effect of education.